Association between multimorbidity and memory-related diseases among middle-aged and older adults: Evidence from the China Health and Retirement Longitudinal Study - Chen, Chen; Zhao, Yihao; Su, Binbin; Wu, Yu; Zhong, Panliang; Zheng, Xiaoying (Frontiers in Public Health, 2023)
Objectives: The aim was to analyze the cross-sectional and longitudinal association between multimorbidity and memory-related diseases (MD) among Chinese middle-aged and older adult. Methods: This study included 8338 subjects participated in the China Health and Retirement Longitudinal Study (CHARLS). Logistic regression and Cox proportional hazards regression models were used to explore the association and effect of multimorbidity on MD. Results: The prevalence of MD in total was 2.52% and the mean multimorbidity count was 1.87. In cross-sectional analysis, comparing with no multimorbidity group, groups of multimorbidity with four or more NCDs were more likely to have MD (OR:6.49, 95%CI: 4.35-9.68). During the 2.7 years of follow-up, 82 cases of MD (1.12%) were reported and participants with multimorbidity were more likely to have new onset MD than no multimorbidity group (HR: 2.93, 95%CI: 1.74-4.96). Conclusions: Multimorbidity is associated with MD among Chinese middle-aged and older adult. And this relationship gradually strengthens with the severity of multimorbidity, which indicates that early prevention for people with multimorbidity may reduce the risk of MD.